The reality of kindergartens spaces and how well they respond to children’s needs and develop their abilities.: Case Study: Batna City - BENYAHIA, Rabah; SAHNOUNE, Tayeb (Journal of Human Sciences, 2020)
During his life, The child passes through many stages and at each stage he acquires certain habits, and abilities that help him to build his personality and form his future. The most important is early childhood, which greatly affects him in different dimensions. Because the quality of the environment in which the child lives, Kindergartens play an important role in his growth according to many considerations. But how responsive is the design of kindergartens spaces and their framing in Algerian cities to the children’s needs? Our research paper seeks to find out the impact of these spaces on children and we concluded that these spaces mostly do not respond to the children’s needs and they have negative effects that can not be controlled after that. We have adopted the investigation method using the observation in situation, questionnaire addressed to educators and parents, interview for the managers and kindergartens children (the sample) in Batna city.